(untitled) (International Journal of Multidisciplinary Research and Explorer, 2021)
The most significant part of face recognition is the input representation. This refers to the transformation of the intensity map to a form of input representation that allows easy and effective extraction of highly discriminative features. The next stage is classification. Although this is an important stage, the popular techniques and their strengths are fairly similar to each other. As such, the choice of classification algorithm does not affect the recognition accuracy as much as input representation. Input representation is the major factor that differentiate face recognition algorithms. It can be approached in 2 manners: a geometrical approach that uses spatial configuration of the facial feature, and a more pictorial approach that uses image-based representation. In this paper a set of different face recognition algorithms are reviewed, and the best practices in this domain are studied and verified.